(untitled) (Medicine Today, 2025)
Introduction: Oral cavity carcinoma (OCC) is a significant health concern, with smoking being a major risk factor. It involves malignancies affecting intraoral structures like the tongue, lips, and gums. Tobacco smoke contains carcinogenic compounds that contribute to DNA damage and oncogenic transformations. This study compares OCC in smokers and non-smokers, focusing on prevalence, progression, and prognosis, to highlight the differences in clinical presentation, histopathology, and outcomes. Objectives: To compare clinical features, tumor sites, staging, histopathology, and treatment outcomes of oral cavity carcinoma in smokers and non-smokers. Method and Materials: This comparative cross-sectional study was conducted at BSMMU from July 2016 to June 2018, involving 120 patients diagnosed with oral cavity carcinoma. Participants were divided into two groups: smokers (60) and non-smokers (60). Data on clinical presentation, tumor staging, and treatment outcomes were collected. Statistical analysis was performed using SPSS, with descriptive and comparative methods to evaluate significant differences between groups. Results: The study included 120 participants with a mean age of 48.2 ± 12.3 years. Of these, 66.7% were male, and 50% were smokers. Smokers reported more pain (83.3%), ulceration (75%), and difficulty eating (58.3%) compared to non-smokers. The tongue was the most common tumor site in smokers (50%). Smokers showed higher rates of advanced-stage cancer, with 41.7% in Stage II. Squamous cell carcinoma was predominant in both groups. Non-smokers had better remission outcomes (66.7% vs. 50%). Conclusion: Smokers with oral cavity carcinoma exhibited more advanced stages, while non-smokers were more likely to present with early-stage cancer. Medicine Today 2025, Vol.37 (2): 193-197